Síndrome Hepatopulmonar - Álvarez Arguedas, Karina (2013)
Hepatopulmonary syndrome (HPS) is an underdiagnosed syndrome that is defined as a clinical triad of advanced liver disease, arterial deoxygenation and intrapulmonary vascular dilatation. It is a rare complication of liver disease of varied etiologies and indicates a poor prognosis. Many theories have been put forward to throw light over its pathogenesis. The major clinical manifestations are arterial hypoxemia, clubbed fingers and spider naevi. Orthodeoxia and platypnea are usual clinical features. A simple non invasive  method to screen HPS is desirable. Contrast enhanced 2D Echo cardiography is the preferred  screening test. No effective medical treatment has been found. Although liver transplant seems feasible to reverse, at least partially, this situation. Long-term oxygen therapy pre and post liver transplant might offer a new therapeutic approach to improve liver function in patients with cirrhosis with hypoxemia.